The Role of Open and Distance Education in Reducing the Educational Gap in Indonesia - Tobondo, Yuyun Alfasius (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2026)
This study analyzed the role of open and distance education (ODE) in reducing the educational gap in Indonesia, particularly between urban and rural areas. The research method was a literature review that collected and analyzed various articles and reports related to ODE in Indonesia and other developing countries. The findings indicated that ODE had great potential to enhance access to education in remote areas; however, this potential has been constrained by uneven technological infrastructure, lack of teacher training, and educational policies that are not yet inclusive. This study recommended improvements in policies to support the development of digital infrastructure and continuous teacher training. Practical recommendations include providing subsidies for devices and Internet access for students in rural areas. While ODE has provided solutions to similar educational gaps in other developing countries, such as India and Nigeria, the implementation of more inclusive policies and enhanced teaching capacity is necessary to optimize its benefits in Indonesia.